2007
DOI: 10.1093/humrep/dem165
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of embryo cultures in an ART laboratory: sources and management

Abstract: Applying the ICSI procedure prevents colonization of the culture dishes by micro-organisms. Infections in IVF culture dishes are mainly caused by bacterial strains insensitive to the antibiotics used or due to yeast colonization by Candida species which frequently reside in the vagina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 13 publications
6
72
1
6
Order By: Relevance
“…A recent review by Pomeroy [7] supports that microbes from the non-sterile IVF culture system and non-sterile oocyte and semen collection process are the most common sources of contamination. In both cases, contamination was observed only in microdrops containing embryos from conventional insemination but not ICSI, which is consistent with Kastrop et al [1], where bacterial contamination was observed in 95 IVF cycles (0.68 %) while no bacterial contamination was observed in 2926 ICSI cycles. Two important sources of contamination during embryo culture are semen and follicular fluids.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A recent review by Pomeroy [7] supports that microbes from the non-sterile IVF culture system and non-sterile oocyte and semen collection process are the most common sources of contamination. In both cases, contamination was observed only in microdrops containing embryos from conventional insemination but not ICSI, which is consistent with Kastrop et al [1], where bacterial contamination was observed in 95 IVF cycles (0.68 %) while no bacterial contamination was observed in 2926 ICSI cycles. Two important sources of contamination during embryo culture are semen and follicular fluids.…”
Section: Discussionsupporting
confidence: 90%
“…To minimize the adverse effects of bacterial contamination on embryonic development, cultured embryos should be removed from microdrops once contamination is identified. In most published reports, embryonic development was poor if embryo culture dishes were contaminated with bacteria [1]. Of the 20 embryos contaminated from the two cases of our report, 11 (55 %) developed to goodquality blastocysts that were either transferable or freezable.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Results of intensive studies regarding the identification of the main sources of such contamination reveled that Escherichia coli (E. coli) and Candida species have caused more than 59 % and 26 % of these contaminations, respectively (6)(7)(8). Among E. coli species, 74 % showed a great resistant to both Penicillin and Streptomycin in the culture medium.…”
Section: Dear Editormentioning
confidence: 99%